Functional expression of the extracellular calcium sensing receptor (CaSR) in equine umbilical cord matrix size-sieved stem cells. - Nicola Antonio Martino; Anna Lange-Consiglio; Fausto Cremonesi; Luisa Valentini; Michele Caira; Antonio Ciro Guaricci; Barbara Ambruosi; Raffaele Luigi Sciorsci; Giovanni Michele Lacalandra; Stephan Joel Reshkin; Maria Elena Dell'Aquila (PLoS ONE, 2011)
Background The present study investigates the effects of high external calcium concentration ([Ca(2+)](o)) and the calcimimetic NPS R-467, a known calcium-sensing receptor (CaSR) agonist, on growth/proliferation of two equine size-sieved umbilical cord matrix mesenchymal stem cell (eUCM-MSC) lines. The involvement of CaSR on observed cell response was analyzed at both the mRNA and protein level. Methodology/principal findings A large (>8 µm in diameter) and a small (<8 µm) cell line were cultured in medium containing: 1) low [Ca(2+)](o) (0.37 mM); 2) high [Ca(2+)](o) (2.87 mM); 3) NPS R-467 (3 µM) in presence of high [Ca(2+)](o) and 4) the CaSR antagonist NPS 2390 (10 µM for 30 min.) followed by incubation in presence of NPS R-467 in medium with high [Ca(2+)](o). Growth/proliferation rates were compared between groups. In large cells, the addition of NPS R-467 significantly increased cell growth whereas increasing [Ca(2+)](o) was not effective in this cell line. In small cells, both higher [Ca(2+)](o) and NPS R-467 increased cell growth. In both cell lines, preincubation with the CaSR antagonist NPS 2390 significantly inhibited the agonistic effect of NPS R-467. In both cell lines, increased [Ca(2+)](o) and/or NPS R-467 reduced doubling time values.Treatment with NPS R-467 down-regulated CaSR mRNA expression in both cell lines. In large cells, NPS R-467 reduced CaSR labeling in the cytosol and increased it at cortical level. Conclusions/significance In conclusion, calcium and the calcimimetic NPS R-467 reduce CaSR mRNA expression and stimulate cell growth/proliferation in eUCM-MSC. Their use as components of media for eUCM-MSC culture could be beneficial to obtain enough cells for down-stream purposes.